Mathematical modeling and thermal–hydrodynamic analysis of vertical water wall in a SCFB boiler with annular furnace. (5th June 2016) - Zhang, Wei; Wang, Huan; Yan, Kai; Zhou, Tuo; Wang, Chang'an; Chen, Kai; Che, Defu
Highlights: A new mathematical model was derived and thermal–hydrodynamic characteristics were analyzed. Connection relationship has an important impact on the distribution of mass flux. Vertical upward parallel tubes present positive flow response characteristic at various operation loads. Abstract: In this study, a mathematical model for a 660 MW SCFB boiler design with annular furnace was deduced and thermal–hydrodynamic analysis was performed to improve the design and operation of water wall. Based on the water wall structure and heat flux distribution of the SCFB boiler, the connection style, pressure drop, mass flux, metal temperature, and phase transition position in water wall were optimally selected and numerically analyzed. The calculation results show that the minimum deviation of mass flux among water wall presents at connection style 1, in which outer-front wall, outer-left (right) wall, inner-front wall, and inner-left (right) wall are connected to the same steam-water separator. The gravitational pressure drop decreases while the frictional pressure drop increases with the rise of fluid temperature. Moreover, vertical upward parallel tubes present positive flow response characteristic with low mass flow rate. The subcooled length and superheated length shrink while the saturated length expands with the reduction of partial loads.